2018
DOI: 10.1002/advs.201800028
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Propelled Motors Navigate Chemical Patterns

Abstract: Very small synthetic motors that use chemical reactions to drive their motion are being studied widely because of their potential applications, which often involve active transport and dynamics on nanoscales. Like biological molecular machines, they must be able to perform their tasks in complex, highly fluctuating environments that can form chemical patterns with diverse structures. Motors in such systems can actively assemble into dynamic clusters and other unique nonequilibrium states. It is shown how chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…The roles of hydrodynamic flow [18][19][20][21][22][23][24], diffused solute [25][26][27][28][29], local phase change [30] and optical shadowing [31,32] as mediators of these interactions have been studied, as well as guidance by nearby boundaries [33][34][35]. Unravelling the dependence of phoretic and chemotactic effects on the surface profiles of catalyst concentration and solute-colloid interaction [8,[36][37][38] and symmetry-based classifications of pair interactions [39] have opened up the possibility of engineering active colloids with desired behaviour [40,41]. We also note that time-periodic behaviours arising through the momentum-like role of the polar orientation [19,[42][43][44] have been observed in thermophoretic colloids in a diverging source of light [45] as well as in paramecium with multiple flagellated protrusions [46].…”
Section: Introductionmentioning
confidence: 99%
“…The roles of hydrodynamic flow [18][19][20][21][22][23][24], diffused solute [25][26][27][28][29], local phase change [30] and optical shadowing [31,32] as mediators of these interactions have been studied, as well as guidance by nearby boundaries [33][34][35]. Unravelling the dependence of phoretic and chemotactic effects on the surface profiles of catalyst concentration and solute-colloid interaction [8,[36][37][38] and symmetry-based classifications of pair interactions [39] have opened up the possibility of engineering active colloids with desired behaviour [40,41]. We also note that time-periodic behaviours arising through the momentum-like role of the polar orientation [19,[42][43][44] have been observed in thermophoretic colloids in a diverging source of light [45] as well as in paramecium with multiple flagellated protrusions [46].…”
Section: Introductionmentioning
confidence: 99%
“…The minimal distance between particles that attract each other is of order l 0 , therefore fixing the hard-core diameter. For comparison, in the experiments described in [25], l 0 ≈10 μm and v 0 ≈1 μm s −1 , resulting in t 0 ≈1 s. Similar molecules have been found with different choices of the mobilities' signs [25,26,32] but we are not aware that the oscillating chain can be formed like that, so we restrict ourselves to the present case.…”
Section: The Model 21 Equations Of Motionmentioning
confidence: 63%
“…In [32], it was shown that Janus particles can be guided in chemical landscapes. Here, we show that the same is possible in self-assembled colloids, with the precaution that the chemical gradient should not break the colloidal molecules apart.…”
Section: Motion In Guiding Fieldsmentioning
confidence: 99%
“…When active sphere dimers are pinned on a 2D layer but free to rotate, strong orientational correlations exist, mainly induced by chemical interactions [92]. If the background medium is chemically inhomogeneous, chemically active microswimmers are able to react to local gradients, or even follow chemical patterns [93]. Time-periodic oscillations of the chemical background medium leads to a periodic dispersion-aggregation transition of active nano-dimers [94].…”
Section: Phoretic Active Particlesmentioning
confidence: 99%